(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Error control consists of error detection and error correction in the communication system. The purpose of this research work is to reduce error in the wireless communication system by using the advantages of both error correction techniques which are forward error correction (FEC) and automatic repeat request (ARQ). Thus, error can be corrected without retransmission and also via retransmission(s) when needed. Combination of FEC and ARQ is known as Hybrid ARQ. In this paper, Hybrid ARQ system is designed using three components which are the irregular repetition code (IRC) as a simple code, bit-interleaved coded modulation with iterative decoding (BICM-ID) as a simple Turbo processing and ARQ. The HARQ system is enhanced by the extended mapping (EM) adopted in the mapping system. The performance of the systems is evaluated in the additive white Gaussian noise (AWGN). The results show the Hybrid ARQ with extended mapping (Hybrid ARQ-EM) outperforms Hybrid ARQ with standard mapping (Hybrid ARQ-SM). Hybrid ARQ-EM achieves low bit error rate BER (10-5) at low signal-to-noise ratio SNR which only 3.03dB close to the theoretical limit. The proposed system Hybrid ARQ-EM achieves 52 percent gain enhancement of SNR gap from the theoretical limit compared to Hybrid ARQ-SM. Hybrid ARQ-EM gives better performance although in worse channel condition.